A comprehensive analysis of the Nigerian economy and 19 industrial sectors - Micheal Stevens and Associates (Lagos, Nigeria : Micheal Stevens and Associates, 1994)
The publication documents significant events and developments of 1997-1999 but also highlights trend for 2000 and forecast for 2001-2003 from the underpinning of the 2000 budget, the 2000-2001 rolling plans and the medium term four years economic plans for 2003 as enunciated by the federal government.
A useful guide for financial analysts, bankers, investors, corporate planners, trade missions, policy makers and multi-lateral agencies
nmn 12/08/16; rpm 07/04/2017
Loans
Keywords: Nigerian economy; Industrial sector; Banking; Insurance; Telecommunications; Industrial sector - Nigeria; Nigeria